2019
DOI: 10.5812/hepatmon.92199
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Non-Alcoholic Fatty Liver Disease in Obese and Overweight Children in the Northwest of Iran

Abstract: Background: Over recent decades, with the increase in the prevalence of childhood overweight/obesity, the prevalence of pediatric non-alcoholic fatty liver disease (NAFLD) has increased. Objectives: The aim of this study was to investigate the prevalence of NAFLD and its predisposing factors in overweight and obese children of Urmia, Northwest of Iran. Methods: In this cross-sectional study, a total of 843 children aged 2 to 19 years were recruited out of 10800 children referred to the Digestive Disease Clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…The search identified 735 references and 127 papers were selected for full‐text review. Finally, 31 articles 14‐44 describing 33 study populations fulfilled the criteria and included in the systematic review and pooled analysis (Figure 1). All the articles were published after 2004, and before April 28, 2021.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The search identified 735 references and 127 papers were selected for full‐text review. Finally, 31 articles 14‐44 describing 33 study populations fulfilled the criteria and included in the systematic review and pooled analysis (Figure 1). All the articles were published after 2004, and before April 28, 2021.…”
Section: Resultsmentioning
confidence: 99%
“…The features of the 31 studies 14‐44 were provided in Table 1. Eighteen studies in Eastern Asia (15 from China, two from Japan, one from Korea), 11 studies in Western Asia (five from Iran, five from Turkey, one from Israel) and two studies in Southern Asia (two from India).…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 shows the feature of selected studies. Of 20 articles, 12 articles assessed NAFLD in adults ( 19 29 ), five studies in obese children ( 30 – 34 ), and three studies in children ( 35 – 37 ). One study was cohort ( 28 ), and the remaining were cross-sectional ( 19 27 , 29 37 ).…”
Section: Resultsmentioning
confidence: 99%
“…One study was cohort ( 28 ), and the remaining were cross-sectional ( 19 27 , 29 37 ). Regarding the quality of included studies, nine studies were considered high (score more than 6 for cross-sectional and more than 9 for cohort studies) ( 20 , 24 26 , 29 , 31 , 33 , 34 , 36 ).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand Gheibi et al, [10] showed that an increase of 10 U/L in ALT, AST and ALK increased the odds of NAFLD 101%, 127% and 2%, respectively. An increase of 10 mg/dL in TG was associated with an 8% increase and also 10 µIu/mL of TSH with a 55% increase in the odds of NAFLD [10].…”
Section: Discussionmentioning
confidence: 97%